1639 Echocardiographic photorealistic imaging of leiomyomatosis intravascularis. (17th January 2020) - Budnik, M; Czub, P; Majstrak, F; Kochanowski, J; Scislo, P; Opolski, G
Abstract: 39-years old female patient was admitted to the Department of Cardiac Surgery because of the suspicion of additional mass in the right atrium (RA). She had no symptoms. Two weeks before she underwent surgery because of the tumours of the uterus and the bladder. Moreover, she was treated for papillary thyroid carcinoma 1 year before. D-dimer levels, NTproBNP and markers of cardiac necrosis weren't elevated. In histopathological examination leiomyomatosis intravascularis was diagnosed. In the transthoracic echocardiography (TTE) we confirmed the presence of additional inhomogeneous, mobile mass in the RA with morphology corresponding to thrombus. Moreover the inferior vena cava (IVC) was also involved. We decided to perform transesophageal echocardiography (TEE). Bicaval view showed that the structure enters through the IVC to the RA and protrude across the tricuspid valve throughout the cardiac cycle. In the photorealistic imaging we could exactly see huge mass that was elongated, mobile, inhomogeneous, had no adhesion with the wall of heart and vein and waved along with the heartbeat (figure 1 A, B). The surgery was performed through median sternotomy. A huge mass with about 30cm length was excised through RA oblique incision, on beating heart with cardiopulmonary bypass (figure 1C).